The Influence of Student Stress Levels and Student’s Mobile Technology Acceptance Levels on Student’s Academic Performance - Buditjahjanto, I.G.P. Asto; Rochmawati, Naim; Diptya Widayaka, Parama; Arwin Dermawan, Dodik; Indah Trisanti, Rosalia; Wildan Habibi, Mohammad (International Journal of Educational Management and Innovation, 2024)
One way to measure education quality is to evaluate students’ learning outcomes. Therefore, this study aims to determine the effect of student stress levels and mobile technology acceptance levels on their learning outcomes. This research method used two methods, namely the Chi-Square method and the correlation method. The Chi-Square method tests the following hypotheses: (a) is there a significant effect between student stress levels and their learning outcomes? (b) is there a significant effect between students’ mobile technology acceptance level and learning outcomes? Meanwhile, the correlation method used to test the hypothesis is as follows: (c) is there a significant correlation between the stress level of students and their learning outcomes? Moreover, (d) Is there a significant correlation between students’ mobile technology acceptance level and learning outcomes? The Chi-Square results for testing hypothesis (a) show that there is a significant influence between the stress level of students and student academic performance. The Chi-Square results for testing hypothesis (b) show no significant effect between the level of mobile technology acceptance and student academic performance. The correlation result for testing hypothesis (c) shows a significant negative correlation between student stress levels and academic performance. The correlation result for testing hypothesis (d) shows a significant positive correlation between the mobile technology acceptance level and students’ academic performance